Professional Languages Alone Do Not Suffice for Successful and Socially Responsible Internal Communication between Different Cultures - Kukovec, Darja; Mulej, Matjaž; Šarotar Žižek, Simona (Naše gospodarstvo/Our economy, 2018)
Successful internal communication in an intercultural environment depends on the organizational culture, business environment, social responsibility, and leaders’ skills. Thus, internal communication and employee adaptation to changing business environments ask what a successful socially responsible internal communication requires. This contribution discusses theoretical foundations of qualitative research, how the organizational culture can define which direction the organization should chose to attain social responsibility, and how internal communication can improve understanding of professional language and be decisive in a working environment. The generated model offers insights into understanding social responsibility and organizational culture to improve internal communication.